Condensyl® and decreases sperm DNA damage which is a risk factor for male infertility: evaluation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006. (5th May 2017) - ; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following an application from Laboratoire Nurilia submitted for authorisation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006 via the Competent Authority of France, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to 'Condensyl ® and decreases sperm DNA damage. High sperm DNA damage is a risk factor for male subfertility/infertility'. Condensyl ® is a fixed combination of opuntia fruit dry extract, N ‐acetyl cysteine, zinc, nicotinamide, vitamins B2, B6, B12 and E, and folic acid. The Panel considers that Condensyl ® is sufficiently characterised. The Panel assumes that the disease that is the subject of the application is male infertility and that the target population for the claim includes males wishing to increase their fertility but excludes males with clinical infertility. The Panel considers that the reduction of DNA sperm damage is a beneficial physiological effect in the context of reducing the risk of male infertility. The applicant provided four human intervention studies conducted in males with clinical infertility, from which no conclusions could be drawn for the scientific substantiation of the claim. The Panel concludes that a cause and effect relationship has not been established between the consumption of Condensyl ® and reduction of DNA sperm damage in the context of reducing the risk of male infertility.